Positron emission tomography molecular imaging for pathological visualization in multiple system atrophy - La Dong; Rui Zhou; Jinyun Zhou; Ke Liu; Chentao Jin; Jing Wang; Chenxi Xue; Mei Tian; Hong Zhang; Yan Zhong (Neurobiology of Disease)
Multiple system atrophy (MSA) is a complex, heterogeneous neurodegenerative disorder characterized by a multifaceted pathogenesis. Its key pathological hallmark is the abnormal aggregation of α-synuclein, which triggers neuroinflammation, disrupts both dopaminergic and non-dopaminergic systems, and results in metabolic abnormalities in the brain. Positron emission tomography (PET) is a non-invasive technique that enables the visualization, characterization, and quantification of these pathological processes from diverse perspectives using radiolabeled agents. PET imaging of molecular events provides valuable insights into the underlying pathomechanisms of MSA and holds significant promise for the development of imaging biomarkers, which could greatly improve disease assessment and management. In this review, we focused on the pathological mechanisms of MSA, summarized relevant targets and radiopharmaceuticals, and discussed the clinical applications and future perspectives of PET molecular imaging in MSA.